(untitled) (Theological Kronos, 2020)
This article pretends to show a non-new reality, violation against women. Our reference to study this situation is the case registered in the Genesis of Dinah, Jacob ́s daughter. We propose the analysis from one of the models of patriarchalism and its affectation to the women. This model exhibits a cruel human condition. Men appear as dictators and avengers from women and other men who had humiliated their honor destination. This article briefly relate the influence of religion in their decisions.